2010
DOI: 10.2174/1876400201003010056
|View full text |Cite
|
Sign up to set email alerts
|

The Utilization of Hyperspectral Imaging for Impurities Detection in Secondary Plastics

Abstract: The systematic identification of impurities inside secondary plastics flow streams can be considered as one of the key issues to certify and to classify waste plastics fed to recycling plants and to perform a full control of the resulting processed fractions, that have to comply with market demands on grade and purity of the recovered products when compared with virgin streams. HyperSpectral Imaging (HSI) can represent an optimal, reliable and low costs answer to reach the previous mentioned goals. HSI is base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…Remarkable is the intensive use of the hyperspectral technology in the food sector as a technique for inspection of a wide range of products investigated, such as fruits and vegetables, meat, fish, eggs and cereals [ 22 ]. Recently, several studies have demonstrated that the hyperspectral analysis can be successfully used in the field of solid waste recycling and treatment, with reference to paper [ 23 ], glass [ 24 ], polymers [ 25 ] and polyolefin [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Remarkable is the intensive use of the hyperspectral technology in the food sector as a technique for inspection of a wide range of products investigated, such as fruits and vegetables, meat, fish, eggs and cereals [ 22 ]. Recently, several studies have demonstrated that the hyperspectral analysis can be successfully used in the field of solid waste recycling and treatment, with reference to paper [ 23 ], glass [ 24 ], polymers [ 25 ] and polyolefin [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…A number of works have demonstrated the NIR-HSI potential in the polymers field for: crystallinity variations in HDPE (high density polyethylene), LDPE (low density polyethylene) and PP (polypropylene) 23 ; contamination of secondary plastics 24 ; miscibility of poly (3-hydroxybutyrate) blends -PHB and PLA 25 ; classification of polymers (PET and PVC) in different life cycles 26 ; maps of the content of diethyleneglycol (DEG) and terminal carboxylic groups (GCT) in a PET fiber sample; 27 and visualization of hydrolysis in polylactide (PLA) 28 . Although this technique can potentially reveal the distributions of the chemical attack on a polymeric surface, as far as we know, NIR-HSI has not been used to identify areas where the attack has occurred nor to evaluate possible preferential paths for these chemical attacks.…”
Section: Introductionmentioning
confidence: 99%
“…There is a vast amount of companies worldwide aimed at recycling PET by already using hyperspectral machinery with NIR and Raman images, together with multivariate models implemented. Many works have dealt with plastic classification by hyperspectral imaging, although only some of them have specially focused on with PET sorting and very few with its separation from PVC …”
Section: Introductionmentioning
confidence: 99%